Pelatihan Pembuatan Tepung Berbahan Dasar Pangan Lokal Dan Pelatihan Pengoperasian Mesin Pengering Tepung Dan Mesin Penepung Pada Kader PKK Negeri Kuralele Dan Trana, Kecamatan TNS, Kabupaten Maluku Tengah - Mailoa, Meitycorfrida; Lopulalan, Cynthia G. C.; Tulalessy, Abraham H. (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Abstrac. This community service activity aims to provide training to PKK cadres in Kuralele Village and Trana Village, TNS Sub-District, Central Maluku Regency on the manufacture of local food-based flour produced by the community and to train the operation of flour and flour drying machines. The method used is the lecture and training method. Through this service program, mothers are trained to make various flours, namely sago flour, corn flour and sweet potato flour. The results of the training showed that mothers enthusiastically participated in the strengths and knowledge about making local food-based flour was well understood. Likewise, the training process for flour drying machines and flour machines can be understood and understood by female cadres and mothers can practice during the activity.